IMPLEMENTATION OF POLYA'S HEURISTIC STRATEGY ON MATHEMATICAL LITERACY ABILITY - M. Iqbal Al-Ihsan; Titis Wulandari; Oktavian Dwi Prasetyo; Chindi Yuliana (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Mathematics is one of the fields of study taught in elementary schools, which some people consider difficult to understand as the basic object of education. So it is necessary to implement efficient and interesting learning for students. This study aims to determine the application of the polya heuristic strategy to students' mathematical literacy problem solving abilities. This study used a quantitative approach with a population of 80 students as primary school students, the sampling technique was cluster random sampling of 50 students, with a two group pretest-posttest design in the form of a control class by providing conventional and experimental method classes by applying heuristic strategies and analyzed using statistical tests. Based on the results of the normality test the data is not normally distributed (Þ = <0.001) therefore, the next step is to do the Wilcoxon test. Based on the test results, the results obtained a significant difference between the results of the pretest and posttest. The average pretest result for the control class was 49.6 and the experimental class was 47. Then after being given treatment, the average posttest score for the control class was 54.8 (conventional method) while the experimental class was 67.6 (polya heuristic strategy). Judging from the posttest scores, both classes showed an increase in learning outcomes, but a large increase was seen in the experimental class that applied the polya heuristic strategy. The polya heuristic strategy has an effect on increasing students' mathematical literacy, therefore this strategy can be implemented in learning mathematics at various levels of education.